2019
DOI: 10.1002/dvg.23309
|View full text |Cite
|
Sign up to set email alerts
|

Proximal fate marker homothorax marks the lateral extension of stalk‐eyed fly Cyrtodopsis whitei

Abstract: The placement of eyes on insect head is an important evolutionary trait. The stalk-eyed fly, Cyrtodopsis whitei, exhibits a hypercephaly phenotype where compound eyes are located on lateral extension from the head while the antennal segments are placed inwardly on this stalk. This stalk-eyed phenotype is characteristic of the family Diopsidae in the Diptera order and dramatically deviates from other dipterans, such as Drosophila.Like other insects, the adult eye and antenna of stalk-eyed fly develop from a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…5 T and U ). Furthermore, we found that similar to Homothorax (Hth) ( 35 ), dve expression is observed in the extended stalk of the stalk-eyed fly where the eyes are placed on laterally extended stalks. This study only showed that dve expression and sequence are highly conserved in stalk-eyed flies ( 36 ).…”
mentioning
confidence: 55%
“…5 T and U ). Furthermore, we found that similar to Homothorax (Hth) ( 35 ), dve expression is observed in the extended stalk of the stalk-eyed fly where the eyes are placed on laterally extended stalks. This study only showed that dve expression and sequence are highly conserved in stalk-eyed flies ( 36 ).…”
mentioning
confidence: 55%
“…The reduced eye phenotype of cul‐4 mutant clones was also accompanied with changes in the placement of eyes on the head (Figure 1). Interestingly, we have reported earlier that placement of eyes on the head of the fly can be due to extension of proximo‐distal axis as seen in the stalk eyed fly (Singh et al, 2019). Furthermore, this extension is due to enhanced Hth expression, which marks the proximal fate.…”
Section: Discussionmentioning
confidence: 91%
“…Meis class protein Hth is also required for maintaining the progenitor population in the anterior region of the eye discs. Hth is expressed in the region, anterior to MF in the undifferentiated proliferating cells (Pai et al, 1998; Singh, Gogia, Chang, & Sun, 2019; Singh et al, 2002; Singh et al, 2011). We found aberrantly high levels of Hth in the cul‐4 mutant eye discs in the posterior as well as anterior region, along with loss of photoreceptors as indicated by loss of Elav positive cells (Figure 5c,c', d,d').…”
Section: Resultsmentioning
confidence: 99%
“…The legs and wings were removed in order to get a clear view of the compound eye. The bright field pictures of adult heads were taken using a Zeiss Apotome Imager Z1 ( Sarkar et al., 2018 ; Singh et al., 2019 ; Wittkorn et al., 2015 ). Eye size was measured using ImageJ software tools ( http://rsb.info.nih.gov/ij/ ).…”
Section: Methodsmentioning
confidence: 99%